P128 Clinical outcomes of equine in vitro embryo production after biphasic IVM - F. Campos-Chillon; M. Bisson; J.L. Altermatt (Journal of Equine Veterinary Science, 2026)

Disentangling vulnerability and exposure to Urban Heat Islands in two French pre-alpine cities - Gilles M. Bisson; Annette E. Casagrande; Julien S. Marinescu; Sandra C. Rome (Theoretical and Applied Climatology, 2026)

When to add a new process to a model – and when not: A marine biogeochemical perspective - Adrian P. Martin; Angela Bahamondes Dominguez; Chelsey A. Baker; Chloé M.J. Baumas; Kelsey M. Bisson; Emma Cavan; Mara Freilich; Eric Galbraith; Martí Galí; Stephanie Henson; Karin F. Kvale; Carsten Lemmen; et al. (Ecological Modelling, 2024)

What data are needed to detect wildfire effects on coastal ecosystems? A case study during the Thomas Fire - Sasha J. Kramer; Kelsey M. Bisson; Catherine Mitchell (Frontiers in Marine Science, 2023)
Wildfires are growing in frequency and severity worldwide, with anthropogenic climate change predicted to worsen the effects of wildfires in the future. While most wildfire impacts occur on land, coastal fires can also affect the ocean via smoke production and ash deposition. The impacts of wildfires on marine ecology and biogeochemistry have been studied infrequently, as it is difficult to conduct fieldwork rapidly and safely during unpredictable natural disasters. Increasingly, remote sensing measurements are used to study the impacts of wildfires on marine ecosystems through optical proxies. Given the optical impacts of smoke and in-water ash, these measurements may be limited in their scope and accuracy. Here, we evaluate the potential and limitations of remote sensing data collected from MODIS-Aqua to describe the effects of wildfires on optics and phytoplankton observations. Using samples collected in the Santa Barbara Channel (California, USA) during the Thomas Fire in December 2017, we found that MODIS-Aqua data were unsuited for interpreting ecosystem effects during a wildfire. Our results identified a persistent overestimation of chlorophyll- a concentration from MODIS-Aqua compared to in situ measurements. Optical models applied to in situ radiometry data overestimated the absorption by colored dissolved organic matter (CDOM) during the wildfire. Satellites will remain an important tool to measure the impacts of wildfires on marine ecosystems, but this analysis demonstrates the importance of in situ sampling to quantify the impacts of wildfires on ocean ecology and biogeochemistry due to the difficulty of interpreting remote sensing data during these events.

P01-04: Development of an Adverse Outcome Pathway (AOP) to assess the neurotoxicity of the exposure to benzo(a)pyrene - M. Bisson; K. Paul; G. Le Noir de Carlan; T. Mille; H. Schroeder (Toxicology Letters, 2023)

Spatial Heterogeneity in Prey Availability, Feeding Success, and Dietary Selectivity for the Threatened Longfin Smelt - Arthur Barros; James A. Hobbs; Malte Willmes; Christina M. Parker; Micah Bisson; Nann A. Fangue; Andrew L. Rypel; Levi S. Lewis (Estuaries and Coasts, 2022)
Food availability is a key determinant of the nursery value of a given habitat for larval and juvenile fishes. Growth, survival, and recruitment success are often inter-correlated and influenced by prey availability and associated feeding success. This is likely true for the threatened population of Longfin Smelt ( Spirinchus thaleichthys ) in the San Francisco Estuary (SFE) which has collapsed in recent decades along with its preferred prey. In years with high precipitation and freshwater outflow, larval Longfin Smelt are found in shallow wetland habitats throughout the SFE, but variation in the availability of food and feeding success in these habitats remains unexplored. To examine spatial variation in the trophic value of different rearing habitats, we quantified variation in prey availability, feeding success, and prey selection for larval and juvenile Longfin Smelt captured in restored tidal marshes, sloughs, and open-water habitats in the northern and southern SFE. Prey abundance varied spatially, with densities approximately tenfold greater in southern sloughs and restored tidal ponds relative to northern and open-water habitats. Feeding success of larval Longfin Smelt was positively correlated with both fish length and prey density. Larval Longfin Smelt fed selectively on the copepod Eurytemora affinis , with larger individuals (> 25 mm total length) exhibiting an ontogenetic diet shift to larger mysid shrimps. Our results suggest that wetland habitats across the SFE vary greatly in their trophic value, with previously unexplored habitats exhibiting the highest densities of prey and the highest foraging success for larval Longfin Smelt.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Pyroclastic density currents at Stromboli volcano (Aeolian Islands, Italy): a case study of the 1930 eruption - A. Di Roberto; A. Bertagnini; M. Pompilio; M. Bisson (Bulletin of Volcanology, 2014)

Rapid terrain-based mapping of some volcaniclastic flow hazard using Gis-based automated methods: a case study from southern Campania, Italy - M. Bisson; R. Sulpizio; G. Zanchetta; F. Demi; R. Santacroce (Natural Hazards, 2010)

Transport Systems of Ventricaria ventricosa: Asymmetry of the Hyper- and Hypotonic Regulation Mechanisms - M. A. Bisson; M. J. Beilby (The Journal of Membrane Biology, 2008)

Volcaniclastic debris-flow occurrences in the Campania region (Southern Italy) and their relation to Holocene–Late Pleistocene pyroclastic fall deposits: implications for large-scale hazard mapping - M. Bisson; M. T. Pareschi; G. Zanchetta; R. Sulpizio; R. Santacroce (Bulletin of Volcanology, 2007)

When is a cell not a cell? A theory relating coenocytic structure to the unusual electrophysiology of Ventricaria ventricosa (Valonia ventricosa) - V. A. Shepherd; M. J. Beilby; M. A. Bisson (Protoplasma, 2004)